The risk of developing more potent fentanyl analogs: a mini review - Bustamante-Elgueta, Benjamín; Andrade, Maikol D.; Quintul, Cristóbal A.; Medina, Daniel A.; Campanini-Salinas, Javier (Frontiers in Pharmacology, 2025)
The global opioid crisis has been accelerated by fentanyl and its analogues, compounds optimized for potency but burdened by vanishingly narrow safety margins. This mini-review integrates chemical, pharmacological, toxicological, and regulatory evidence to interrogate the “more-potent-is-better” paradigm. We synthesize in vivo data across representative analogues, highlighting those compounds that are much more potent than fentanyl and the risks of their use. Moreover, several analogues exhibit markedly low protection indices, indicating that doses producing analgesia lie perilously close to those causing hypoventilation. Reversing the effects of overdose remains pharmacologically feasible, although in vitro evidence suggests that antagonists such as naloxone may require higher or repeated doses to counteract ultra-potent fentanyl analogs. Forensic and public-health signals, rapid marketplace turnover, metabolic complexity, polysubstance exposure, and episodic mass poisonings, underscore the risks of continuing to chase potency. We also map the regulatory gap at the health–security nexus and flag dual-use concerns, including AI-enabled design of ultra-potent scaffolds with poor therapeutic windows. We argue for a strategic pivot: prioritize intrinsic safety over potency by targeting wider therapeutic windows, mechanism-level dissociation of analgesia from respiratory depression, standardized antagonist requirements, and class-aware scheduling that preserves legitimate research. Redirecting discovery toward safety-first opioids is both scientifically tractable and ethically imperative.